ORGANISING LOGISTICS IN ALFAMART SAMBAS SUB DISTRICT, TUMUK MANGGIS VILLAGE - Anisa Jufri; Hadenan Towpek (Review of International Economy and Finance, 2025)
This study aims to evaluate and analyse the organisation of logistics at Alfamart located in Sambas Sub-district, Tumuk Manggis Village. In this study, a descriptive qualitative approach was used using observation methods, in-depth interviews with store managers, logistics staff, and documentation analysis. The results showed that Alfamart Tumuk Manggis Village has implemented a structured logistics management system, including goods receipt, storage, and distribution to sales shelves. However, some of the challenges faced include limited storage space, fluctuations in customer demand, and coordination with suppliers. A product category-based storage system and the use of inventory management software have helped with operational efficiency, but there are still constraints in managing stock-outs and seasonal products. This research suggests increasing warehouse capacity, optimising information technology, and regular training for logistics staff to improve the performance of better logistics organisation. With these improvements, it is expected that Alfamart Sambas Sub-district will be able to improve the efficiency and effectiveness of its logistics operations so that it can provide optimal service to customers.